Deciphering the effect of algae sources on the formation of algal-bacterial granular sludge: Endogenous versus exogenous algae. (20th August 2022) - Liu, Zhe; Ning, Fangzhi; Hou, Yiwen; Zhang, Dan; Yang, Rushuo; Wang, Jiaxuan; Zhang, Aining; Chen, Yiping; Liu, Yongjun
Abstract: As a key factor affecting the granulation of symbiotic sludge, the evaluation of the influence of algae sources on the ABGS system is expected to further optimize the cultivation of ABGS. In this study, formation of algal-bacterial granular sludge (ABGS) cultivated with endogenous algae and exogenous algae was comparatively investigated. During ABGS formation, the presence of algae facilitated the settleability improvement and biomass growth. ABGS cultivated with endogenous algae achieved a faster granulation (39 days) than that with exogenous algae (46 days). Inoculating exogenous algae could significantly improve the nutrient removal efficiency at the start-up stage. Tightly-bound extracellular polymeric substances (TB-EPS) were crucial for ABGS formation and maintenance, especially protein (PN) components. More EPS enriched in the mature ABGS enhanced by endogenous algae. The spatial distribution of protein and α-D-glucopyranose was obviously affected by algal sources. During ABGS formation, there was a directional selection in algal species, and the operation condition of the system was the key factor affecting the structure of algae community. The effect of algae sources on the bacterial community structure of ABGS took time to manifest. Correlation analysis showed that endogenous algae contributed more to the metabolism and property improvement of sludge than exogenous algae. Graphical abstract: Image 1 Highlights: ABGS cultivated by the endogenous algae achieved a faster granulation. Inoculating EX-A obviously improved the nutrient removal at the initial stage. Mature ABGS cultivated with endogenous algae could secrete more EPS. Algae source was not the dominant factor in determining the algal community in ABGS. The genes related to metabolism were more enriched by endogenous algae in mature ABGS.